O papel da atividade lúdica como motivadora da aprendizagem da língua inglesa: análise de um livro didático - Patriota, Luis Ferdinando da Silva (2013)
This work aims at analyzing the activities presented in the book On Stage for junior high school students, which was selected by IFRN, as well as checking out the students interest for play activities. We have come from the point that playing activities can contribute to the increasing of motivation for the teaching of English (BROUGERE, 1999; WRIGHT, BETTERIDGE, BUCKBY, 2006; LANGRAN e PURCELL, 1994). At first place, our research is a document analysis and in second place, it is an action research. We have proposed two questionnaires for the participants of this work, all of them are High school students at IFRN-Campus Zona Norte, in order to check out their interests and the degree of motivation for the English learning before and after the carrying out of play activities. The obtained data also showed that the students became more motivated and interested in the classes after working with play activities, and most of the students agreed with the inclusion of these activities in the selected course book. The result of our work proved the benefits of play activities according to researches available in the literature about this subject. From the results acquired in the present work, we suggest that play activities should be included in English course books, even when they are addressed to High School teaching in order to help increasing the motivation for the learning of a foreign language